2015
DOI: 10.1371/journal.pone.0126466
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Cells Hijack PRC2 to Modify Multiple Cytokine Pathways

Abstract: Polycomb Repressive Complex 2 (PRC2) is an epigenetic regulator induced in many cancers. It is thought to drive tumorigenesis by repressing division, stemness, and/or developmental regulators. Cancers evade immune detection, and diverse immune regulators are perturbed in different tumors. It is unclear how such cell-specific effects are coordinated. Here, we show a profound and cancer-selective role for PRC2 in repressing multiple cytokine pathways. We find that PRC2 represses hundreds of IFNγ stimulated genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 65 publications
(81 reference statements)
6
27
0
Order By: Relevance
“…3G). These results are consistent with previous observations in cancer cell lines that depletion of SUZ12, a subunit of the EZH2/1-PRC2 complex, resulted in the expression of a class of ISGs whose promoters exhibited bivalent (H3K27me3 and H3K4me3) histone methylation markers (54). The results are also complemented by analyses of data sets (GEO data set GSE81267) published by Qi et al (28) where treatment of Karpas422 cancer cells with a novel inhibitor targeting the PRC2 subunit EED (EED226) induced antipathogen gene cascades that parallel the inflammatory and stress pathways shown here ( Fig.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…3G). These results are consistent with previous observations in cancer cell lines that depletion of SUZ12, a subunit of the EZH2/1-PRC2 complex, resulted in the expression of a class of ISGs whose promoters exhibited bivalent (H3K27me3 and H3K4me3) histone methylation markers (54). The results are also complemented by analyses of data sets (GEO data set GSE81267) published by Qi et al (28) where treatment of Karpas422 cancer cells with a novel inhibitor targeting the PRC2 subunit EED (EED226) induced antipathogen gene cascades that parallel the inflammatory and stress pathways shown here ( Fig.…”
supporting
confidence: 93%
“…Thus, these inhibitors amplify cellular antiviral responses and contribute to the induction of immune cell responses in a context-dependent manner. The results are analogous to the synergistic/enhanced induction of ISGs in cells treated with both EZH2/1 inhibitors and IFN-␥, lipopolysaccharide, IL-1␤, or tumor necrosis factor alpha relative to treatment with each compound alone (54).…”
Section: Discussionmentioning
confidence: 56%
“…We identified genes induced upon type I and II interferon treatment in GBM cells and found that 40% of the EZH2-activated genes were induced by interferon treatment. Consistent with previously published data, a significant fraction (~40%) of the EZH2repressed genes also showed induction on interferon treatment (20). This suggests that EZH2 represses ISGs directly and also activates them indirectly by repressing miRNAs that target them.…”
Section: Discussionsupporting
confidence: 90%
“…Polycomb proteins and miRNAs have independently been implicated in the regulation of interferon genes (16,20,21). miRNAs have also been shown to activate expression of interferon pathway genes via repression of polycomb proteins (21).…”
Section: Discussionmentioning
confidence: 99%
“…Cytokines can be grouped by structure into different families, as can and their receptors. It had been reported that the cytokine-cytokine receptor interaction gene set may induce cancer (41) and was upregulated in cancer cachexia (42); these changes should result in the development of markers for early diagnosis and a better understanding of the conditions of a tumor. Mak et al (43) revealed that the marked upregulation of genes involved in cytokine-cytokine receptor interactions were consistently detected in tumor cell lines.…”
Section: Discussionmentioning
confidence: 99%